The glycemic status determines the direction of the relationship between red cell distribution width and HbA1c - Tsilingiris, Dimitrios; Makrilakis, Konstantinos; Barmpagianni, Aikaterini; Dalamaga, Maria; Tentolouris, Anastasios; Kosta, Ourania; Eleftheriadou, Ioanna; Liatis, Stavros (Journal of diabetes and its complications, 2021)
Aims - Available studies conducted on heterogenous populations on the association between the erythrocyte distribution width (RDW) and HbA1c have reported a positive, negative or neutral relationship. The aim of the present study is to investigate the debated relationship between RDW and HbA1c among hematologically healthy individuals with and without type 2 diabetes mellitus (T2DM). - Methods - Paired measurements of RDW and HbA1c of 183 hematologically healthy individuals (100 without DM, 83 with T2DM) were obtained. The association of HbA1c with a) hematologic parameters (hemoglobin, log[ferritin], RDW) and b) factors related to glycemia (BMI, fructosamine, FPG) was examined within each group separately and in the sum of the study sample. - Results - There was a significant positive correlation of RDW with HbA1c among those without DM while the opposite was true among individuals with T2DM (r = 0.315, p = 0.001 and r = −0.275, p = 0.011). In the T2DM group a significant negative correlation with fructosamine was noted (r = −0.274, p = 0.012) which was absent among normoglycemic individuals. Among those without DM the association between HbA1c and RDW remained significant after adjustment for all tested parameters. In the population with T2DM the significance was attenuated after including glycemia-related factors values. In multivariable regression in the sum of the study sample, the interaction between diabetes status and RDW as regards HbA1c was significant [unstandardized correlation coefficient − 0.397 (−0.646 to −0.147), p = 0.002] and remained significant after adjustment for multiple potential confounders. - Conclusions - Among individuals without DM, the RDW likely reflects the non-glycemic interference on HbA1c values, while in T2DM RDW may serve as an indirect index of glycemia and dysmetabolism.